Quis erit, erit: fatalism and ayanmo in ancient Greek and traditional Yoruba philosophical thoughts (2018)
Fatalism is a philosophical concept generally used to refer to the belief that man is powerless to do or change anything in the face of future events which are believed to be inevitable. The idea is that there is no point trying to control the future. Thus, the concept of fatalism often leads to the altitude of resignation in the conviction that man does not have control over the events in his life, hence ’what will be will be'. Many ancient Greek philosophers, especially the Stoics, used the term moirai for fatalism and argue in support of and against the concept. For instance, one of the famous arguments of the ancient Greek philosophers is that if an event is fated, it would be futile to make an concerted effort to avoid or bring it about. The Yorùbà, like the Greeks use words such as àyànmó (destiny). kadara(fate), àkosilè (predetermination) among others to describe the futility of trying to change or control what has been predetermined or predestined. Therefore, the concept of fatalism is greatly reflected in various traditional Yorùbà proverbs and songs. The question which this paper focuses on is: is man really helpless in the face of fatalism? This paper engages a comparative and critical analysis method of enquiry to react to this question